Consensus document of the Spanish Nutrition Society (SEÑ) on nutritional strategies in sports - Mielgo-Ayuso, J.; Macho-González, A.; Úbeda, N.; Sánchez-Oliver, A. J.; Martínez-Ferrán, M.; Fernández-Lázaro, D.; Aparicio-Ugarriza, R.; Roche, E.; González-Gross, M. (Nutrients, 2025)
Introduction: Nutrition plays a fundamental role in sports performance by influencing energy availability, recovery, and training adaptation. In recent years, different dietary strategies have gained popularity among athletes, although the evidence supporting their efficacy is inconsistent. Objective: This consensus document, developed under the auspices of the Spanish Society of Nutrition, aims to provide a critical overview of the most relevant nutritional strategies currently used in sports and to offer evidence-based practical recommendations for both professional and recreational athletes, coaches, and health professionals. Methods: A narrative review was conducted following standardized scientific procedures by a multidisciplinary panel of experts. The analyzed strategies included high-carbohydrate, low-carbohydrate, ketogenic, intermittent fasting, plant-based, Paleolithic, and carbohydrate periodization diets. Each strategy was assessed based on its physiological rationale, evidence of performance in endurance, strength/power, sprint, aesthetic, weight category, and team sports, practical applications, and potential risks. Results: The available evidence shows that no single dietary strategy can be universally recommended for all athletes. High carbohydrate availability remains the most consistent approach for sustaining performance in endurance and high-intensity efforts. Low-carbohydrate and ketogenic diets enhance fat oxidation but often compromise exercise economy at competitive intensity levels. Intermittent fasting may improve body composition and metabolic health; however, it requires careful adaptation. Well-planned plant-based diets can support performance, although attention to certain nutrients (e.g., B12, iron, and omega-3) is essential. Paleolithic diets improve metabolic parameters but show limited direct evidence of athletic performance. Carbohydrate periodization is a promising tool for combining metabolic adaptations with competitive demands. Conclusions: Nutritional strategies should be individualized according to the athlete`s sport, training phase, and personal context. Professional guidance is crucial for minimizing risks and optimizing benefits. Further well-designed, long-term studies on athletes are needed to resolve the current controversies.